2008
DOI: 10.1029/2007jc004514
|View full text |Cite
|
Sign up to set email alerts
|

Wave‐driven setup and alongshore flows observed onshore of a submarine canyon

Abstract: [1] The effect of alongshore variations in the incident wavefield on wave-driven setup and on alongshore flows in the surfzone is investigated using observations collected onshore of a submarine canyon. Wave heights and radiation stresses at the outer edge of the surfzone (water depth %2.5 m) varied by up to a factor of 4 and 16, respectively, over a 450 m alongshore distance, resulting in setup variations as large as 0.1 m along the shoreline (water depth %0.3 m). Even with this strong alongshore variability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 38 publications
2
64
1
Order By: Relevance
“…Similar to previous results [van der Westhuysen, 2010;Gorrell et al, 2011;and many others], the model skillfully predicts the wave heights observed in 7 ( Model simulations suggest strong spatial inhomogeneity in wave heights ( Figure 6a) and directions ( Figure 6b) onshore of the complex bathymetry, similar to nearshore waves in other locations [Apotsos et al, 2008;Chen et al, 2015;and others] suggest that the size and location of the region of flow separation are sensitive to bathymetry and shoreline shape, which may not be accurate near the separation region. Model skill is higher a few km to the west (e.g., x=3.3 km, Figure 8b), away from the separation region.…”
Section: A Model-data Comparisonssupporting
confidence: 70%
See 1 more Smart Citation
“…Similar to previous results [van der Westhuysen, 2010;Gorrell et al, 2011;and many others], the model skillfully predicts the wave heights observed in 7 ( Model simulations suggest strong spatial inhomogeneity in wave heights ( Figure 6a) and directions ( Figure 6b) onshore of the complex bathymetry, similar to nearshore waves in other locations [Apotsos et al, 2008;Chen et al, 2015;and others] suggest that the size and location of the region of flow separation are sensitive to bathymetry and shoreline shape, which may not be accurate near the separation region. Model skill is higher a few km to the west (e.g., x=3.3 km, Figure 8b), away from the separation region.…”
Section: A Model-data Comparisonssupporting
confidence: 70%
“…Breaking waves dissipate energy while transferring momentum flux to the water column. In the surf zone, the time-averaged wave-driven forcing raises water levels near the shoreline [Longuet-Higgins and Stewart, 1964], producing alongshore varying sea levels and currents [Apotsos et al, 2008;Shi et al, 2011; and, in the case of obliquely incident waves, driving alongshore currents in the direction of wave propagation [Longuet-Higgins, 1970;Thornton and Guza, 1986;Guza et al, 1986;Feddersen et al, 1998;and many others]. The wave-orbital velocities and wave-generated mean currents can transport sediment and act as a mechanism for shoreline evolution references therein; and many others].…”
Section: Introductionmentioning
confidence: 99%
“…6). Waves that approach the coast obliquely mostly produce longshore current rather than high set-up because the cross-shore component of the radiation stress is mostly responsible for set-up (Apotsos et al, 2008). The highest set-up occurs when waves approach the coast almost perpendicularly (i.e.…”
Section: Almost-incident Wavesmentioning
confidence: 99%
“…Tidal elevation, channel depth, significant wave height, energy-weighted wave direction, and period corresponding to the centroid of the sea-surface elevation spectrum for 4 dates. threshold for breaking [Thornton and Guza, 1983;Raubenheimer et al, 1996;Apotsos et al, 2008a], but not in the deeper channel (Figure 4.6C). When waves break, their momentum flux is transferred to the water column, driving an increasing water level or setup [Longuet-Higgins and Stewart, 1964;Lentz and Raubenheimer, 1999;Raubenheimer et al, 2001, and many others] (Figure 4.6D, dashed contours).…”
Section: Flow Patternsmentioning
confidence: 99%
“…When incident waves propagate over alongshore-variable bathymetry, spatial variations in breaking-wave-driven setup lead to non-uniformities in the alongshore flow and offshore-directed flows near bathymetric depressions [Sonu, 1972;Oltman-Shay et al, 1989;Svendsen and Putrevu, 1990;Putrevu et al, 1995;Sancho, 1998;Slinn et al, 2000;Apotsos et al, 2008a, Hansen et al, 2015.…”
Section: Introductionmentioning
confidence: 99%